Evaluating the Learning Curve Associated with Laparoscopic Left Hemicolectomy for Colon Cancer. Issue 4 (April 2013) - Yamamoto, Masashi; Okuda, Junji; Tanaka, Keitaro; Kondo, Keisaku; Asai, Keiko; Kayano, Hajime; Masubuchi, Shinsuke; Uchiyama, Kazuhisa
The role of laparoscopic surgery for transverse and descending colon cancer remains controversial. The aim of the present study was to characterize the learning curve for laparoscopic left hemicolectomy including the splenic flexure and to identify factors that influence this learning curve. Data from 120 consecutive patients undergoing laparoscopic left hemicolectomy for transverse and descending colon cancer including the splenic flexure between December 1996 and December 2009 were analyzed. Patients undergoing resection combined with cholecystectomy, hepatectomy, hysterectomy, or gastrectomy were excluded. Operative time was analyzed using the moving average method. The operative time, conversion rate, and postoperative complication rate were evaluated among four groups based on the number of cases required for analysis of operative time. In addition, risk factors that influenced conversion to open surgery were analyzed. Operative time for left hemicolectomy decreased with increasing case number with stabilization at 30 cases. There was no significant difference in the conversion rate or postoperative complications over time. Significant factors for conversion to open surgery were T stage (odds ratio [OR], 5.56; 95% confidence interval [CI], 1.5 to 27.4) and previous abdominal surgery (OR, 5.38; 95% CI, 1.6 to 20.2). The learning curve for laparoscopic left hemicolectomy is steep. Thus, surgeons in the early part of this curve should carefully select patients to allow them to build experience in a stepwise manner. Laparoscopic surgery may become the gold standard for management of colon cancer regardless of stage or tumor location.